(untitled) (American Journal of Islam and Society, 2012)
In Jewish Identities in Iran, Mehrdad Amanat tries to unearth the roots of Iranian Jews converting to both Islam and the Baha’i faith starting with the Safavid period in the sixteenth century. Admitting a personal interest in the project (his family converted from Judaism to the Baha’i faith), Amanat searches for answers in, among many other resources, autobiographies written by members of all faiths. Included are the memoirs of Mash’allah Farivar, son of the chief rabbi and dayan (judge) of the Jewish community of Shiraz, and Fazel Mazandarani’s multi-volume history of the Babi–Baha’is. Missing from the extensive fourteen-page bibliography, however, is the field research conducted by Laurence Loeb in Shiraz, Outcast: Jewish Life in Southern Iran, and multiple volumes of The History of Contemporary Iranian Jews, edited by Homa and Human Sarshar. Relatively short for a research of this magnitude (210 pages), the reader might feel rushed through the historical events. The first chapter, “The Jewish Presence in Pre-Islamic and Medieval Iran,” covers centuries of Iranian Jewish life in just twenty pages. Under such headings as “Jews in the pre-Islamic Period,” “Economic and Cultural Spheres,” “Encounters with Other Religions,” “The Early Islamic Period,” “The Militant Jews of Isfahan,” “Early Conversions to Islam,” “Religious Diversity under Mongol Rule,” and “The Emergence of Jewish Notables,” the author barely touches the surface of each issue. Amanat’s research is nevertheless meticulous and often cites multiple examples to reveal a cause for conversion in the later chapters ...